EFFECTIVENESS OF DRY EXTRACT MAHONI SEED CONSUMPTION ON BLOOD SUGAR LEVEL IN DIABETES MELLITUS PATIENTS - Ganda Ardiansyah; Henny Purwandari; Heni Prastika Damayanti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
An increase in blood sugar levels caused diabetes mellitus, and various other health complications. One of the herbal therapy approaches can be used by consuming mahogany seeds which are believed to reduce blood glucose levels. The purpose of this study was to determine the effectiveness of consuming mahogany seeds to reduce blood sugar levels. This was a quasi-experiment with non-randomized control group pretest-posttest design conducted on March 24-26 2020. A sample of 22 respondents was divided into 2 groups: treatment group and control group selected by purposive sampling. The data was collected by observation. The data was analysed by Paired t-test. The treatment group before consuming the dry extract of Mahogany seeds (Mean=258.27; SD= 46.98), and after consuming the dry extract of Mahogany seeds (Mean= 185.36; SD= 38.85). In the control group, before consuming the extract of Mahogany seed ekring (Mean= 224.27; SD= 14.73), and after consuming Mahogany seed extract (Mean= 213.27; SD=6.75). It was statistically significant (p= 0.001). Consumption of dry extract of Mahogany seeds effectively reduces blood sugar levels in patients with Diabetes Mellitus. Consumption of mahogany seeds can be used as a complementary therapy in nursing to reduce blood sugar.